Spectrum of Autoimmune Diseases in Children with Celiac Disease: A Single Center Cross-Sectional Study from A Tertiary Childcare Facility of South Punjab, Pakistan: Spectrum of Autoimmune Diseases in Children with Celiac Disease - Irshad, Sundus; Aslam, Irum; Talib, Abu; Khosa, Ghazi; Sheikh, Aslam; Zahid, Saima (Pakistan Journal of Health Sciences, 2025)
Celiac disease (CD), an autoimmune disorder triggered by gluten ingestion, is increasingly recognized for its association with a higher prevalence of other autoimmune conditions in children, underscoring the need for more exploration. Objectives: To evaluate the spectrum of autoimmune diseases (AIDs) in children with CD. Methods: This cross-sectional study was performed at the Department of Gastroenterology, Hepatology and Nutrition, The Children’s Hospital and The Institute of Child Health, Multan, Pakistan, from September 2023 to December 2024. Children aged between 1-12 years and having CD were analyzed. The presence of AIDs was explored utilizing physical and clinical examination, along with relevant laboratory and radiographic studies. Results: In a total of 167 children with CD, 95 (56.9%) were male. The mean age was 6.01 ± 3.31 years. The most frequent presenting complaints were abdominal pain, diarrhea, and weight loss, noted in 70 (41.9%), 65 (38.9%), and 53 (31.7%) children, respectively. AIDs were diagnosed in 38 (22.8%) children, while the most common AIDs were autoimmune thyroiditis, type-1 diabetes mellitus (T1DM), asthma, and autoimmune hepatitis, found in 11 (6.6%), 7 (4.2%), 4 (2.4%), and 4 (2.4%) children, respectively. Low monthly family income (p=0.013), or severe CD type (p=0.010), were found to have a significant association with AIDs. Conclusions: Children with CD have a high prevalence of associated AIDs, with autoimmune thyroiditis, T1DM, asthma, and autoimmune hepatitis being the most commonly observed conditions. The severity of CD appears to be a contributing factor to the development of AIDs.